Growth Performance of Live Fish Feed: Artemia salina in Different Supplemental Feeds in Aquarium Culture - Khadka, Nabin; Khadka, Raksha; Mandal, Ram Bhajan; Adhikari, Ashok (Journal of Agriculture and Environment, 2023)
Artemia is an excellent live feed for newly hatched fish and crustaceans gained a unique position in the aquaculture system. Brine shrimp is a non-selective filter feeder, so different locally available source feeds should be evaluated as potential food source for their control mass culturing. The experiment was carried out to study the effect of different supplement feeds on the growth performance of Artemia at Central Fisheries Promotion and Conservation Centre, Baalaju, Kathmandu from December 2021 to February 2022. The experiment was carried out in complete randomized design (CRD) with four treatments, each treatment consisting four replications. Four treatments consist different combination of supplement feed i.e., T1: (spirulina + rice bran), T2: (soyabean + rice bran), T3: (Mustard oilcake + rice bran), T4: (Yeast + rice bran). All supplement feed contains 25% CP and feed diet was supplied by 2% of body weight. In terms of growth and yield performance parameters, significant effect was recorded on average length, individual weight and total biomass. Also, significant effect was recorded on survivability and density. However, no significant effect was recorded on CP content of Artemia biomass. T1 recorded the maximum average length (8.7±0.21 mm), individual weight (0.0028±0.0001 gm), and biomass (1.79±0.069 gm/L) whereas lowest average length (7±0.08 mm), individual weight (0.0013±0.0002 gm) and biomass (0.61±0.005 gm) was recorded in T4. Also, T1 recorded the maximum density (633.8±3.62), and survivability (70.8±0.5) whereas lowest density(467.9±4.26) and survivability (58.0±1,71) found in T4. Hence it can be concluded that the combination of spirulina and rice bran was best supplement diet and can be applied in the cultivation of Artemia for best growth performance and biomass Production in aquarium condition.